Effect of TNF-α −308G/A (rs1800629) Promoter Polymorphism on the Serum Level of TNF-α Among Iraqi Patients with Generalized Vitiligo - Ahmed R; Sharif D; Jaf M; Amin DM (Dove Medical Press, 2020)
Ronak Ahmed,1 Dana Sharif,2 Mohammad Jaf,1,3 Dashty Mohammed Amin3 1Dermatology Unit, College of Medicine, University of Sulaimani, Sulaymaniyah, Iraq; 2Department of Medicine, College of Medicine, University of Sulaimani, Sulaymaniyah, Iraq; 3Medical Laboratory Science, KOMAR University of Science and Technology, Sulaymaniyah, Iraq; 4Kurdistan Board of Dermatology, Kurdistan Board for Medical SpecializationCorrespondence: Ronak AhmedDermatology Unit, College of Medicine, University of Sulaimani, Sulaymaniyah, IraqTel +9647501176757Email dr-ronaksa@hotmail.comBackground: Vitiligo is a chronic acquired pigmentary disorder of the skin; it results from immunological distruction of functioning melanocytes. The cytokine TNF-α plays a central role in the initiation of melanocyte apoptosis in vitiligo. Single nucleotide polymorphism (SNP) in the promoter region of the gene coding for serum TNF-α may affect its production.Objective: The aim of this study is to assess serum TNF-α as a risk factor for generalized vitiligo among Iraqi patients and to rule out that polymorphism at the − 308 position affects serum TNF-α.Materials and Methods: This case–control study was conducted at Sulaymaniyah Dermatology Teaching Center (SDTC), Iraq. Serum concentration of TNF-α was measured using enzyme linked immunosorbent assay (ELISA) technique in 80 patients with generalized vitiligo and 40 clinically healthy controls. The amplification refractory mutation system polymerase chain reaction (ARMS–PCR) technique was used for detection of TNF-308G/A gene polymorphism. TNF-α level correlated with TNF- 308G/A gene polymorphism. Serum concentration and TNF -308G/A gene polymorphism have been analyzed in correlation with demographic features and clinical characteristics of patients with generalized vitiligo.Results: Statistically significant elevation of serum TNF-α seen in patients compared to a control group (p-value 0.01). Significantly higher TNF-α level (p-value 0.01) found among patients with active generalized vitiligo. Elevated serum levels of TNF-α were significantly associated with both TNFA1 (TNF-308G) allele (p-value 0.04) and TNFA2 (TNF-308A) allele (p-value 0.03). TNF-α − 308GA polymorphism was not affected by demographic features and clinical characteristics of patients with generalized vitiligo.Conclusion: TNF-α in the serum is a risk factor for generalized vitiligo among Iraqi patients. Patients with active vitiligo have a higher serum TNF-α level. No difference was found between serum level of TNF-α with TNF-α polymorphism at position − 308 (TNF − 308). This involves substituting G allele for the A allele.Keywords: generalized vitiligo, serum TNF-α − 308G/A promoter polymorphism, Iraq